Innovation, markets and sustainable energy : the challenge of hydrogen and fuel cells - Pogutz, Stefano; Russo, Angelantonio; Migliavacca, Paolo (Cheltenham, UK : Edward Elgar, 2009)
Adopting a cross-sectional and international perspective, this title analyses the implications of introducing fuel cell technologies into the industrial system and explores the complexity of market development for new technological solutions
Keywords: Hydrogen as fuel; Fuel cells; Renewable energy sources -- Economic aspects; Renewable energy sources -- Technological innovations